Genetic Variability of Grain Sorghum (Sorghum bicolour L. Monech) Genotypes under Drought Stress Conditions - E. Idris, Atif; Elmunsor, Ismael Ibrahim; Abuali, Atif Ibrahim (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Twenty two genotypes of grain sorghum (Sorghum bicolour L. Monech.) were evaluated at College of Agricultural Studies, Sudan University of Science and Technology, Shambat, during two successive summer seasons of 2012 and 2013 to estimate the genetic variability among different grain sorghum genotypes under drought stress conditions and to identify the most tolerant genotypes under drought stress conditions. The genotypes were evaluated using a split plot arrangements based on a randomized complete block design with three replications. Two water treatments were applied, namely; well-watering (irrigated every 7 days) and drought stress (irrigated every 21 days). Genotypic coefficient of variation, heritability and drought tolerance parameters were determined. The results showed that, significant differences were detected between the genotypes for most of studied characters. Drought stress was severe enough to cause significant reduction in yield and yield components and most of the studied characters, yield and yield components were more sensitive to drought stress compared than other growth characters. High genotypic coefficient of variation and heritability were exhibited by dry weight, days to 50% flowering and days to maturity. A wide range of genetic variability was detected by genotypes for drought tolerance. According to their high yield and tolerance under drought conditions, the genotypes HSD8849 and HSD7511 could be used for further breeding program to improve drought tolerance in sorghum.